The effect of ABCB1 polymorphisms on the outcome of breast cancer treatment - Tulsyan S; Mittal RD; Mittal B (Dove Medical Press, 2016)
Sonam Tulsyan,1 Rama Devi Mittal,2 Balraj Mittal1 1Department of Genetics, 2Department of Urology and Renal Transplant, Sanjay Gandhi Postgraduate Institute of Medical Sciences, Lucknow, IndiaAbstract: The ABCB1 gene encodes a permeability glycoprotein, which is one of the most extensively studied human adenosine-triphosphate (ATP)-dependent efflux transporters. Permeability glycoprotein is expressed in the apical membranes of tissues such as intestine, liver, blood–brain barrier, kidney, placenta, and testis and contributes to intracellular drug disposition. It is also highly expressed in tumor cells conferring drug resistance, which is one of the major problems in the efficacy of cancer chemotherapy treatment. ABCB1 is highly polymorphic, and three well-known single-nucleotide polymorphisms such as 1236C>T, 2677G>T/A, and 3435C>T have been found to be associated with altered messenger RNA levels, protein folding, and drug pharmacokinetics. Many association studies and meta-analyses have demonstrated the clinical impact of ABCB1 polymorphisms in breast cancer treatment outcomes with respect to therapeutic response, chemotoxicity, and overall survival. Therefore, the aim of this review was to evaluate the effects of ABCB1 polymorphisms on the outcome of breast cancer treatment which, in future, would be important for tailoring individualized anticancer therapy.Keywords: ABCB1, P-glycoprotein, polymorphisms, breast cancer treatment, chemotherapy, response, drug resistance